"Allow natural death" is not equivalent to "do not resuscitate": a response. Issue 12 (28th November 2008) - Chen, Y-Y; Youngner, S J
Abstract : Venneman and colleagues argue that "do not resuscitate" (DNR) is problematic and should be replaced by "allow natural death" (AND). Their argument is flawed. First, while end-of-life discussions should be as positive as possible, they cannot and should not sidestep painful but necessary confrontations with morality. Second, while DNR can indeed be nonspecific and confusing, AND merely replaces one problematic term with another. Finally, the study's results are not generalisable to the populations of physicians and working nurses and certainly do not support the authors' claim that there is a movement to replace DNR with AND.